Group exercises for patient with mobility limitation - Ghabeljoo M (Iran University of Medical Sciences, 1991)
Extract: physical mobility and exercise are necessary for people health. For patient with mobility limitation this issue has more importance because these exercises help them to return to normal function more effectively. Since the individual planning for each patient is not time effective, so we could plan group exercises and perform properly in orthopedic wards. The important goals of this plan including: 1- prevention of pneumonia due to immobility and its circulation complication. 2- Keep the joints mobility. 3- Preparation of patient for walking with walker. 4- Determine the patients who need to individual helps for active and passive motions.